Inclusion and early years practice - Brodie, Kathy; Savage, Keith (London ; New York : Routledge, 2015)
'Inclusion is a difficult, complex issue for which there are no off-the-shelf answers. To be an effective practitioner it is necessary to identify what makes each situation and circumstance unique and use this knowledge to develop strategies and approaches that are appropriate. This timely new text examines the key perceptions, perspectives and concepts around inclusion in the Early Years. Drawing on real-life experiences of practitioners, it considers the questions practitioners are likely to come across in their professional lives and how they might genuinely go about meeting the needs of all the children in their care. The book covers all aspects of inclusion including special educational needs, gender and sexuality, multiculturalism, multilingualism, Roma and traveller communities and economic wellbeing. Each chapter features: - Case studies to develop reflective thinking - Boxed examples to illustrate key points - Questions to promote discussion and debate - Annotated further reading lists With case studies drawn from current research and thinking points which encourage reflective practice, this book will be essential reading for students on early childhood studies programmes and early years foundation degrees that wish to become reflective and critically aware practitioners'--
Includes bibliographical references and index.
Keywords: Inclusive education -- Great Britain; Early childhood education -- Great Britain